Studies on Morphological Transformation of BALB/3T3-Derived Clones by Murine Leukemia Virus - Smith, Helene S. (1976)
We have described a cell line, UC1-B, derived spontaneously from BALB/3T3 mouse embryo cells, which, unlike the standard BALB/3T3, are morphologically transformed and produce bizarre viral forms in response to murine leukemia virus. Although UC1-B and BALB/3T3 are morphologically similar, and both form contact-inhibited monolayers at confluence, the UC1-B cells are partially transformed because: they grow to a slightly higher saturation density than 3T3 cells, they grow in medium lacking serum growth factors, and they produce tumors in mice. Another clone, 12A-3, derived from BALB/3T3, also transforms and produces bizarre viral forms after infection with murine leukemia virus. Unlike UC1-B cells, the 12A3-8 cells are identical in growth properties to BALB/3T3; therefore, a partially altered morphology is not required for the induction of transformation by murine leukemia virus.